Second victim experiences of healthcare providers after adverse events: A cross-sectional study - Le Crenis Mathebula; Celia J. Filmalter; Joyce Jordaan; Tanya Heyns (AOSIS, 2022)
Background: Adverse events in healthcare are inevitable as most treatments and investigations have the potential to cause harm. Healthcare providers often witness or are involved in adverse events, putting them at risk of becoming second victims, which may further impact patient safety. Aim: The researchers report on the physical and psychological symptoms experienced by healthcare providers following adverse events during patient care as well as their perceptions of the quality of support received and the desired forms of support following adverse events. Setting: A single secondary public hospital in the Limpopo province, South Africa. Methods: Using total population sampling, healthcare providers were invited to anonymously participate in a cross-sectional survey using the Second Victim Experience and Support questionnaire to assess experiences after adverse events and desired forms of support. Results: Healthcare providers (N = 181) experienced more psychological distress (mean = 2.97, standard deviation [SD] = 1.33) than they experienced physical distress. Most healthcare providers relied on non-work-related support (mean = 4.08, SD = 1.19). Healthcare providers reported that adverse events influenced their perceptions of professional self-efficacy (mean = 2.71, SD = 0.94) and mostly desired support in the form of discussing the event with supervisors or managers (mean = 3.72, SD = 1.37). Conclusion: Healthcare providers in different clinical settings are at risk of suffering second victim effects. Health institutions should offer support to all victims of adverse events. Contribution: The information offered could enable healthcare management to modify existing practices to a non-punitive style, improve communication and provide better support following adverse events.